2022
DOI: 10.1042/bsr20220986
|View full text |Cite
|
Sign up to set email alerts
|

Peimine ameliorates pulmonary fibrosis via the inhibition of M2-type macrophage polarization through the suppression of P38/Akt/STAT6 signals

Abstract: Peimine, a bioactive substance isolated from Chinese medicine Fritillaria, can potentially suppress pulmonary fibrosis (PF); however, its therapeutic mechanism remains unclear. Recent evidence suggests the participation of M2-type macrophages in the pathogenesis of PF. The present study aimed to investigate the effect of peimine on a bleomycin (BLM)-induced PF rat model and the underlying mechanism of this effect. After BLM administration, peimine was administered to rats from day 29 to day 42, with pirfenidon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…Although IFN-γ is the principal cytokine exerting a protective role in immune response against microbial infections by activating macrophages [ 54 ], a constant and continuous hyperproduction of this molecular signal leads to a deleterious state of macrophage chronic activation, namely chronic inflammation. The high levels of CCR7 and CD86 proteins and the contemporary low levels in pSTAT6 and CD206 protein expression let us speculate that this inflammatory state is both a cause and an effect of a M1 phenotype prevalence [ 55 , 56 ]. Further evidence supporting this hypothesis comes from the observed high intracellular concentration of iron.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although IFN-γ is the principal cytokine exerting a protective role in immune response against microbial infections by activating macrophages [ 54 ], a constant and continuous hyperproduction of this molecular signal leads to a deleterious state of macrophage chronic activation, namely chronic inflammation. The high levels of CCR7 and CD86 proteins and the contemporary low levels in pSTAT6 and CD206 protein expression let us speculate that this inflammatory state is both a cause and an effect of a M1 phenotype prevalence [ 55 , 56 ]. Further evidence supporting this hypothesis comes from the observed high intracellular concentration of iron.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, after stimulating macrophages with JWH-133, we observed an increase in pSTAT6 protein, which is a key molecule in the transition from M1 to M2 phenotype. As many authors already suggested, the phosphorylation of this protein regulates the M2 polarization, so it could be considered not only an M2 phenotype marker, but a marker of polarization progress toward the M2 type [ 55 , 56 ]. Our results highlight the promising possibility to target the CB2 receptor in DMD, leveraging anti-inflammatory effects mediated by macrophages, the most representative cells of the immune system, to improve short- and long-term outcomes in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Peimine and peiminine, when administered alone, significantly inhibit the upregulation of TLR4/MAPK/NF‐κB signaling pathway‐related proteins and the activation of IL‐17, and they can resist inflammation in mice with lipopolysaccharide‐mediated acute lung injury (Liu, Zhen, et al, 2022). Additionally, peimine has a potential inhibitory effect on pulmonary fibrosis, which can improve pulmonary fibrosis by inhibiting STAT6, p38MAPK, and Akt signals and suppressing the M2 polarization of macrophages (Cai et al, 2022). Peiminine improves lung function, alleviates pulmonary fibrosis, and prevents the exacerbation of COPD via regulating EGFR and MLC2 signaling pathways (Ma et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, peimine has a potential inhibitory effect on pulmonary fibrosis, which can improve pulmonary fibrosis by inhibiting STAT6, p38MAPK, and Akt signals and suppressing the M2 polarization of macrophages (Cai et al, 2022). Peiminine improves lung function, alleviates pulmonary fibrosis, and prevents the exacerbation of COPD via regulating EGFR and MLC2 signaling pathways (Ma et al, 2019).…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…An in vivo study confirmed that PM could prevent PF by inhibiting macrophage M2 polarization. 18 However, the detailed mechanism of PM on PF remains unclear. To explore the therapeutic effect of PM on PF and its mechanism of action, this study first used BLM to induce PF in mice and then treated the mice with PM.…”
Section: Introductionmentioning
confidence: 99%